(3GdKZQ GdHSGe aj PcQ ef hdi bVGA GdTGes - (3eMeO Hf Ydj Hf CMeO Hf Ydj Hf NeGQhjg Hf Whdhf GdOeTbqj GdUGdMj GdMfaj, TeS GdOjf , J (B953 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi JYRR HGdbOQI hGdceGd s
(3BNQgG (B:s
(3hJhdjI GdTGe GdTQja eMeO Hf YHOGdChd, GdeMQhb HgG MdhG CejQ , hcGf bGVjkG HMdH GdTgHGA s
(3GdUaMI GdCNjQI ecedI HNW BNQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B291s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B125 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdJGQjNs